2019
DOI: 10.1039/c8ra10241d
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity of boron-doped graphane under high pressure

Abstract: Under high-pressure, the most stable two configurations of B-doped graphane are phase-α and phase-β, and pressurization can increase their Tc significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The results indicate that the T c of B-doped dimane is not sensitive to the B substitutional sites. However, the T c of B-doped diamane is much lower than that of B-doped graphane (45-77 K) [51,52]. This is partially due to the fact that there are only one sp 3 hybridized C layer in the B-doped graphane, which may give larger electron-phonon coupling parameter (λ = 0.72) than that of B-doped diamane (λ = 0.53) with two sp 3 hybridized C layers.…”
Section: Superconductivitymentioning
confidence: 96%
“…The results indicate that the T c of B-doped dimane is not sensitive to the B substitutional sites. However, the T c of B-doped diamane is much lower than that of B-doped graphane (45-77 K) [51,52]. This is partially due to the fact that there are only one sp 3 hybridized C layer in the B-doped graphane, which may give larger electron-phonon coupling parameter (λ = 0.72) than that of B-doped diamane (λ = 0.53) with two sp 3 hybridized C layers.…”
Section: Superconductivitymentioning
confidence: 96%
“…[8] Many new hydrides are synthesized, [9][10][11] and record of the highest T C is broken by hydrides in rapid succession. [12][13][14][15] To explore new hydrides with T C above room temperature, the investigation into the mechanism of the high T C of H 3 S has been a hot topic and fruitful. [16][17][18][19] It is suggested that the superconductivity of H 3 S can be attributed to a conventional phonon-mediated mechanism, as it exhibits strong covalent bonds giving rise to large electron-phonon coupling.…”
Section: Introductionmentioning
confidence: 99%
“…However, C2/m symmetric TlFeSe 2 is the ground-state phase at ambient condition. Doping and pressuring have been proved effective in modulating superconductivity, both of which come down to affecting the superconducting pairing in essence [10][11][12][13][14][15][16][17]. By applying pressure, apart from conspicuous reconstructions, possible superconductivity with a critical-temperature (T c ) ∼ 2 K above 30 GPa was experimentally observed in TlFeSe 2 , [18] very different from the T c of FeSe SCs which is around 30 K. [19,20] Thus, TlFeSe 2 would serve as a platform for probing into the affecting factors on regulating T c and revealing the essence of superconductivity.…”
Section: Introductionmentioning
confidence: 99%